Extracellular vesicles as potential biomarkers and treatment options for liver failure: A systematic review up to March 2022 - Lu, Wang; Tang, Huixin; Li, Shanshan; Bai, Li; Chen, Yu (Frontiers in Immunology, 2023)
Extracellular vesicles (EVs) carrying functional cargoes are emerging as biomarkers and treatment strategies in multiple liver diseases. Nevertheless, the potential of EVs in liver failure remain indistinct. In this systematic review, we comprehensively analyzed the potential of EVs as biomarkers of liver failure and the therapeutic effects and possible mechanisms of EVs for liver failure. We conducted a systematic review by comprehensively searching the following electronic databases: PubMed, Web of Science, Embase and Cochrane Central Register of Controlled Trials from inception to March 2022. The used text words (synonyms and word variations) and database-specific subject headings included “Extracellular Vesicles”, “Exosome”, “Liver Failure”, “Liver Injury”, etc. A total of 1479 studies were identified. After removing 680 duplicate studies and 742 irrelevant studies, 57 studies were finally retained and analyzed. Fourteen studies revealed EVs with functional cargoes could be used to make diagnosis of liver failure and provide clues for early warning and prognostic assessment of patients with liver failure. Forty-three studies confirmed the administration of EVs from different sources alleviated hepatic damage and improved survival through inhibiting inflammatory response, oxidative stress as well as apoptosis or promoting hepatocyte regeneration. In conclusion, EVs and their cargoes can be used not only as superior biomarkers of early warning, early diagnosis and prognostic assessments for liver failure, but also as potentially effective treatment option for liver failure. In the future, large-scale studies are urgently needed to verify the diagnostic, predictive and therapeutic value of EVs for liver failure.